SLO Adoption and Usage in Site Reliability Engineering - McCoy, Julie; Forsgren, Nicole (O'Reilly Media, Inc., 2020)
Site Reliability Engineering (SRE)-a framework for managing enterprise software systems, first developed at Google-helps lower operational costs, enhance development productivity, and increase feature release. But if service-level objectives (SLOs) aren't part of your SRE strategy, you're leaving value on the table. This practical report details why and how to make SLOs, service-level indicators (SLIs), and error budgets critical components of your SRE practice. Drawing on results from Google's recent SLO Adoption and Usage Survey, along with real-world case studies, this guide walks you through defining and determining an acceptable level of reliability and using it to set expectations for stability and better manage system changes. Whether you're an SRE, executive, developer, or architect, you'll learn how to improve your SRE practices by taking an SLO and error-based approach to measuring and managing your service. Understand common service-level terminology, including objectives, indicators, agreements, and error budgets Build SLOs and SLIs step by step Use error budgets to align and jointly make decisions about reliability and development velocity See how Schlumberger and Evernote implemented SLOs and used the insights gained to manage their businesses.